Microglia-Derived Exosomal microRNA-151-3p Enhances Functional Healing After Spinal Cord Injury by Attenuating Neuronal Apoptosis via Regulating the p53/p21/CDK1 Signaling Pathway - Li, Chengjun; Qin, Tian; Liu, Yudong; Wen, Haicheng; Zhao, Jinyun; Luo, Zixiang; Peng, Wei; Lu, Hongbin; Duan, Chunyue; Cao, Yong; Hu, Jianzhong (Frontiers in Cell and Developmental Biology, 2022)
Spinal cord injury (SCI) is a catastrophic event mainly involving neuronal apoptosis and axonal disruption, and it causes severe motor and sensory deficits. Due to the complicated pathological process of SCI, there is currently still a lack of effective treatment for SCI. Microglia, a type of immune cell residing in the central nervous system (CNS), need to respond to various stimuli to protect neuronal cells from death. It was also reported that microRNAs (miRNAs) had been identified in microglia-derived exosomes that can be taken up by neurons. However, the kinds of miRNAs in exosome cargo derived from microglia and the underlying mechanisms by which they contribute to neuroprotection after SCI remains unknown. In the present study, a contusive SCI mouse model and in vitro experiments were applied to explore the therapeutic effects of microglia-derived exosomes on neuronal apoptosis, axonal regrowth and functional recovery after SCI. Then, miRNA analysis, rescue experiments and luciferase activity assays for target genes were performed to confirm the role and underlying mechanism of microglia-derived exosomal miRNAs in SCI. We revealed that microglia-derived exosomes could promote neurological functional recovery by suppressing neuronal apoptosis and promoting axonal regrowth both in vivo and in vitro. MicroRNA-151-3p is abundant in microglia-derived exosomes and is necessary for mediating the neuroprotective effect of microglia-derived exosomes for SCI repair. Luciferase activity assays reported that P53 was the target gene for miR-151-3p and that p53/p21/CDK1 signaling cascades may be involved in the modulation of neuronal apoptosis and axonal regrowth by microglia-derived exosomal microRNA-151-3p. In conclusion, our data demonstrated that microglia-derived exosomes (microglia-Exos) might be a promising, cell-free approach for the treatment of SCI. MicroRNA-151-3p is the key molecule in microglia-derived exosomes that mediates the neuroprotective effects of SCI treatments.